Teaching exceptional children : foundations and best practices in inclusive early childhood education classrooms - Bayat, Mojdeh (b, 2017)
Teaching Exceptional Children is ideal for introductory courses in early childhood special education at the graduate and undergraduate level.
Includes bibliographical references and index.
Keywords: Special education teachers -- Handbooks, manuals, etc; Learning disabled children -- Education; Developmentally disabled children -- Education; Individualized instruction